PENGARUH BRISK WALKING EXERCISE TERHADAP PENURUNAN KADAR GULA DARAH PADA PASIEN DM TIPE II DI RUMAH SAKIT GRANDMED LUBUK PAKAM - Kardina Hayati (Jurnal Penelitian Keperawatan Medik, 2021)
The silent killer disease that often occurs in humans was Diabetes Mellitus (DM). DM sufferers were generally unaware of this disease condition and when complications were known to have occurred. Control of basic sugar levels was the right way to reduce complications that occur in sufferers. The research objective was to determine the effect of walking exercise on changes in blood glucose levels in patients with type 2 diabetes mellitus. The Methode that used at this research was a pre-experimental design with a one group pretest-posttest design approach. There were 30 people of population of this study with diabetes mellitus taken using a simple random sampling technique which was 21 respondents. The Data analysis using Paired Samples T-test. The results showed that before doing all respondents exeperienced, blood glucose levels before walking exercise 21 people (100 %). After walking exercise decreased by 21 people (66,3%). Paired Sample T- test results obtained a probability value (p = 0.00) <(α = 0.05) which means H1 is accepted. Physical exercise which is carried out 3 times 30 minutes per week can reduce the risk for type 2 DM sufferers to have uncontrolled blood glucose level. Physical exercise is highly recommended for people with type 2 diabetes. To maintain body functions to work properly, the stability of blood sugar levels needs to be maintained.